Descriptive analysis of the economic burden of treatment resistance in a major depressive episode. (1st February 2020) - Cai, Qian; Sheehan, John J.; Wu, Bingcao; Alphs, Larry; Connolly, Nancy; Benson, Carmela
Abstract: Objectives: To assess characteristics and healthcare costs associated with pharmacologically treated episodes of treatment-resistant depression (TRD) in patients with major depressive disorder (MDD). Methods: Patients aged ≥18 years with continuous health plan enrollment for ≥12 months before and after a newly observed MDD diagnosis (observed between 1 January 2010 and 31 December 2015) were included in this retrospective claims-based analysis. A pharmacologically treated episode was defined as beginning at the date of the first MDD diagnosis and ending when a gap of 180 days occurred between MDD diagnoses, or when a gap of 180 days occurred following the end of the antidepressant (AD)/antipsychotic (AP) drug supply. When such a gap occurred, the episode end date was determined to be either the date of the last MDD diagnosis or date of the end of AD/AP drug supply, whichever was later. An episode was considered TRD if ≥3 AD regimens occurred. Episode duration, medication regimens used, and relapse hospitalization were reported for TRD and non-TRD MDD episodes. Total all-cause and per-patient-per-month (PPPM) healthcare costs (in 2016 $) were estimated. Results: Of 48, 440 patients identified with ≥1 AD-treated MDD episode, the mean (SD) age was 39 (15) years, and 62% were female. Of all episodes, 7% were TRD, with a mean duration of 571 (285) days vs. 200 (198) days for non-TRD MDD episodes. Mean total all-cause costs were $19, 626 ($44, 160) for TRD and $7440 ($25, 150) for non-TRD MDD episodes. Conclusions: Results show TRD episodes are longer and costlier than non-TRD MDD episodes, and that higher costs are driven by episode duration. Longer episodes imply protracted suffering for patients with TRD and increased burden on caregivers. Effective intervention to shorten TRD episodes may lessen disease burden and reduce costs.